analisis respon imunitas terhadap infeksi sars-cov-2 pada manusia - Nainggolan, Edward Anderson; Tamba, Ernawaty; Susilowati, Rina Priastini (Jurnal MedScientiae, 2024)
Understanding the immune response to COVID-19 is critical to help develop appropriate management. Understand the description and response of the immune system that is formed in humans through COVID-19 infection. Conduct a critical review of research journals on the immune response to SARS-CoV-19. Search for articles in research journal databases using the keywords COVID-19, SARS-CoV-2, and Immunity. COVID-19 patients have increased serum cytokine levels (TNFα, IL-2, IL-6, IL-10, IFNγ) compared with healthy patients. IL-6, IL-10, and CRP increased significantly with disease severity. The number of T cells decreases in COVID-19 patients, especially those who are more severe. There were no significant differences in antibody titers based on gender, age, or BMI in post-vaccine individuals. Smokers had significantly lower antibody titers after the second dose of vaccination. COVID-19 patients experience a decrease in the number of lymphocytes and an increase in CRP and cytokines such as TNFα, IL-2, IL-6, IL-10, and IFNγ, especially in severe cases. A positive correlation exists between CRP and IL-10. The number of T cells such as CD4+T and CD8+T also decreases in COVID-19 patients, especially those who are more severe. This could be a diagnostic and prognostic marker for COVID-19.